2014
DOI: 10.1002/anie.201410858
|View full text |Cite
|
Sign up to set email alerts
|

Cationic RAFT Polymerization Using ppm Concentrations of Organic Acid

Abstract: A metal-free, cationic, reversible addition-fragmentation chain-transfer (RAFT) polymerization was proposed and realized. A series of thiocarbonylthio compounds were used in the presence of a small amount of triflic acid for isobutyl vinyl ether to give polymers with controlled molecular weight of up to 1×10(5) and narrow molecular-weight distributions (Mw /Mn <1.1). This "living" or controlled cationic polymerization is applicable to various electron-rich monomers including vinyl ethers, p-methoxystyrene, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
191
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(198 citation statements)
references
References 36 publications
6
191
0
1
Order By: Relevance
“…This has been shown for radical polymerizations in the so-called RAFT (reversible addition-fragmentation chain-transfer) process 12 for ring-opening polymerizations in the 'immortal ring-opening polymerization' process 13 in coordinative chain-transfer polymerization 14,15 and, recently, in cationic RAFT polymerization 16 . In principle, any degenerative reversible chain-transfer polymerization requires only catalytic quantities of the propagating species as these are transferred quickly from one polymer chain to the next through a degenerative transfer and so simulate a quasi-simultaneous chain growth.…”
mentioning
confidence: 89%
“…This has been shown for radical polymerizations in the so-called RAFT (reversible addition-fragmentation chain-transfer) process 12 for ring-opening polymerizations in the 'immortal ring-opening polymerization' process 13 in coordinative chain-transfer polymerization 14,15 and, recently, in cationic RAFT polymerization 16 . In principle, any degenerative reversible chain-transfer polymerization requires only catalytic quantities of the propagating species as these are transferred quickly from one polymer chain to the next through a degenerative transfer and so simulate a quasi-simultaneous chain growth.…”
mentioning
confidence: 89%
“…It also indicates the high stability of the thioether terminal even during the work-up procedures and MALDI-TOF-MS analysis unlike the thioester terminals obtained by the cationic RAFT polymerization of IBVE. 38 Upon increasing the concentration of TfOH, the acetal terminals originating from the methanol used for quenching the polymerization became visible in both the 1 H NMR and MALDI-TOF-MS spectra ( Figure 2B). A further increase of [TfOH] 0 makes these peaks larger ( Figure 2C).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…3 A relatively large C tr was obtained with 1 (C tr = 5.31, entry 3), which gave the narrowest MWD among the various thioethers examined, whereas it was lower than that with the trithiocarbonate RAFT agent (7; C tr = 7.68, entry 12) previously reported by us. 38,41 A similar oxygen ether or acetal compound (8) that is the adduct of methyl vinyl ether and methanol resulted in a higher molecular weight, a broader MWD (M w /M n ∼ 1.8), and, thus, a low constant (C tr = 1.55, entry 13). Thus, the sulfur atom is necessary for the effective degenerative chain-transfer process via the formation of the sulfonium intermediate.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Kamigaito et al have recently reported another type of "switchable" transfer agent that allowed interconvertible polymerization of acrylates and vinyl ethers by both living cationic or radical polymerization, using a Lewis acid or azo initiator, respectively. 101,102 It is also worth noting that ab initio investigations have suggested the use of fluorine as the stabilizing Z group can afford CTAs that may also be capable of successfully mediating the polymerization of monomers with disparate reactivity. 103,104 However, to date, this possibility has been only rarely explored, perhaps as a result of the rather challenging synthesis required to obtain CTAs with fluorine Z groups.…”
Section: Monomer Class Specificity Of Raft Agentsmentioning
confidence: 99%